Transitional care for patients with acute stroke-A priority‐setting project - Liss Marita Solbakken; Birgitta Langhammer; Antje Sundseth; Therese Brovold (Wiley, 2022)
Abstract Background The scope of this priority‐setting process is communication and collaboration in transitional care for patients with acute stroke. Actively involving persons with stroke and their family caregivers is important both in transitional care and when setting priorities for research. Established priority‐setting methods are time‐consuming and require extensive resources. They are therefore not feasible in small‐scale research. This article describes a pragmatic priority‐setting process to identify a prioritized top 10 list of research needs regarding transitional care for patients with acute stroke. Methods A pragmatic priority‐setting approach inspired by the James Lind Alliance was developed. It involves establishing a user group, identifying the research needs through an online survey, analysing and checking the research needs against systematic reviews, culminating in an online prioritization of the top 10 list. Results The process was completed in 7 months. A total of 122 patients, family caregivers, health personnel and caseworkers submitted 484 research needs, and 19 users prioritized the top 10 list. The list includes the categories 'patients and caregivers' needs and health literacy', 'health personnel's common understanding', 'information flow between health personnel and patients and caregivers', 'available interventions and follow‐up of patients and caregivers', 'interaction and collaboration between health personnel and caseworkers across hospital and primary healthcare' and 'disabilities after stroke'. Conclusion This paper outlines a pragmatic approach to identifying and prioritizing users' research needs that was completed in 7 months. The top 10 list resulting from this priority setting process can guide future research relating to communication and collaboration during the transition from hospital to the community for patients with stroke. Patient and Public Contribution Members of three stroke organizations participated in the advisory group. They gave feedback on the scope and the process, distributed the surveys and prioritized the top 10 list. Persons with stroke and their caregivers submitted research needs in the survey.